Research Progress of Natural Polymers in Wastewater Treatment - Li, Xiang; Yang, Baojun; Feng, Li; Zheng, Huaili; Zeng, Guoming; Wu, Pei (Mini-Reviews in Organic Chemistry, 2019)
With the development of industry, urbanization, increasingly stringent environmental protection requirements, and strengthening of people’s environmental awareness, green treatment of pollutants has become a research hotspot in the field of environmental protection. Accordingly, the study on natural non-toxic polymers has received increasing attention from researchers. This paper aims to provide the present research progress of natural polymers in environmental engineering, including the striking characteristics and modification methods of the most well-known natural polymers, as well as their applications in environmental protection field. Concluding remarks and future trends are also pointed out.
Keywords: natural polymer